Liquidity management of commercial banks operating in Poland - Majkútová, Natalia (2019)
This Thesis evaluated the level of liquidity risk and the tools used to minimize such risk in Polish commercial banks. The evaluation of the liquidity of banks in Poland consists of three parts. Firstly, the changes in funding gap, which is a measure of funding liquidity risk, in the period from 2003 to 2018 of commercial Polish banks was assessed. The main finding of this analysis was that the funding liquidity risk was significantly lower before the Global Financial Crisis than during any years since the crisis. Secondly, analysis of the liquidity ratios level since 2008 until 2018 was presented. The last part of the analysis demonstrated the analysis of linear regression of certain macroeconomic factors (unemployment, and inflation) and funding gap